2004
DOI: 10.1007/s00246-004-0776-4
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Interstage Death After the Norwood Procedure

Abstract: Operative survival after the Norwood procedure has significantly improved during the past 10 years. However, there remains attrition among Norwood survivors before reaching planned second-stage palliation. The purpose of this study was to evaluate potential risk factors for interstage mortality among Norwood survivors. All patients undergoing the Norwood procedure at the Medical University of South Carolina from January 1996 through January 2001 were retrospectively reviewed. Patient and procedural variables w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
83
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(87 citation statements)
references
References 15 publications
4
83
0
Order By: Relevance
“…A few other studies have also examined interstage death, deaths that occur between being discharged to home post-Norwood procedure and admission for the stage II procedure, and reported an incidence of two to 20 % (Rudd et al 2014;Hehir et al 2008;Furck et al 2010;Ghanayem et al 2012;Simsic et al 2004). The Milwaukee group has reported an excellent interstage survival outcome of 98 % for interstage survival using their multidisciplinary home monitoring system (Rudd et al 2014) while other groups are still reporting significant interstage mortality (Furck et al 2010;Simsic et al 2004).…”
Section: Interstage Mortalitymentioning
confidence: 99%
See 1 more Smart Citation
“…A few other studies have also examined interstage death, deaths that occur between being discharged to home post-Norwood procedure and admission for the stage II procedure, and reported an incidence of two to 20 % (Rudd et al 2014;Hehir et al 2008;Furck et al 2010;Ghanayem et al 2012;Simsic et al 2004). The Milwaukee group has reported an excellent interstage survival outcome of 98 % for interstage survival using their multidisciplinary home monitoring system (Rudd et al 2014) while other groups are still reporting significant interstage mortality (Furck et al 2010;Simsic et al 2004).…”
Section: Interstage Mortalitymentioning
confidence: 99%
“…The Milwaukee group has reported an excellent interstage survival outcome of 98 % for interstage survival using their multidisciplinary home monitoring system (Rudd et al 2014) while other groups are still reporting significant interstage mortality (Furck et al 2010;Simsic et al 2004). A nested case-control study looked at 33 HLHS patients who experienced interstage deaths compared to 99 HLHS survivors (Hehir et al 2008).…”
Section: Interstage Mortalitymentioning
confidence: 99%
“…The review included eight retrospective reviews of surgical cases, [23][24][25][26][27][28][29][30] four retrospective cohort studies, [31][32][33][34] two case-control studies 35,36 and one randomised controlled trial that was reported in two papers. 26,37 Only three studies 29,36,37 included a prospective element.…”
Section: Study Selectionmentioning
confidence: 99%
“…Although study designs differed, all studies were rated as good quality ( Table 1); studies that were assigned a lower rating failed to address some potential confounding factors. Ten reports were of patients with a functional single-ventricle (SV) diagnosis, 23,24,[26][27][28]30,33,[35][36][37] which was most often HLHS. Fourteen papers involved patients who underwent cardiac surgery during the first year of life and the remaining study 31 included cardiac patients operated up to the age of 18 years with results provided separately for each age group.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation